Strategi Pelayanan Kesehatan Berbasis Islam untuk Meningkatkan Kepuasan Pasien di RS Muhammadiyah - Deviyanti, Luckyana; Sa’adah, Nur Hikmatu; Herlina, Herlina; Maududi, Abul A'la Al (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to examine the implementation of Islamic-based healthcare services in Muhammadiyah hospitals by focusing on the integration of Islamic values in improving service quality and patient satisfaction. Using a qualitative approach through library research, this study reviews various literature related to Islamic healthcare concepts, the theology of Al-Ma'un, service quality, and the modernization of healthcare systems. The findings indicate that Islamic values such as amanah (trustworthiness), ihsan (excellence), ta’awun (mutual assistance), and justice can be effectively applied within modern healthcare practices. These values significantly strengthen the dimensions of empathy, reliability, and assurance, which contribute to higher levels of patient satisfaction. Moreover, Muhammadiyah hospitals have developed innovations such as e-hospital systems, telemedicine, and sharia-based information systems to address modernization challenges. The study concludes that integrating Islamic principles into healthcare services can create a more humanistic, professional, and equitable healthcare model.